‘Auctor beatae pacis...’: The Image of Tsar Alexander I in Marcin Poczobut-Odlanicki’s Paeans - Kowal, Jolanta (Senoji Lietuvos literatūra, 2021)
Marcin Poczobut-Odlanicki had a wide range of professional activities. He was not only a renowned astronomer, mathematician, theologian, educational reformer, editor, publisher, and rector, but also a poet. Unfortunately, the latter occupation of the Jesuit from Vilnius has not attracted scholars’ attention, probably because his poetry was not of a high artistic standard.The same can be said of the two occasional poems in honour of Tsar Alexander I. Although Poczobut wrote them in the last decade of his life, there is no doubt that today they have a unique value as a document of that epoch and reflect the public mood in Lithuania at the beginning of the nineteenth century.The educated rector of the Principal School of the Grand Duchy of Lithuania had high hopes for the new Russian tsar’s support for the activities of the institution under his leadership.This article also attempts to place Poczobut’s panegyric poems in the context of other texts of this type written in honour of Alexander I at that time.
Keywords: panegyric; occasional poetry; Tsar Aleksander I; Marcin PoczobutOdlanicki; Vilnius University; Lithuania